Answer:
x = -13 and y = -5
Step-by-step explanation:
Given the below equations;
![\begin{gathered} -2y=-42-4x \\ -x-2y=23 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z50i5g17zcxiozl3lqr7vsewc9g81dtpnc.png)
Let's go ahead and solve simultaneously using the substitution method.
From the 2nd equation;
![\begin{gathered} -x=2y+23 \\ \therefore x=-2y-23 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d0sisld23tr9wfodlss713j5z7j8ikrxoa.png)
Let's put x = -2y - 23 into the 1st equation and find y;
![\begin{gathered} -2y=-42-4(-2y-23) \\ -2y=-42+8y+92 \\ -2y-8y=50 \\ -10y=50 \\ y=-(50)/(10) \\ \therefore y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6f55ri0svc9whiyvnlsmgeft4qvytten7g.png)
Let's substitute the value of y into x = -2y - 23 and find x;
![\begin{gathered} x=-2(-5)-23 \\ =10-23 \\ \therefore x=-13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nrf3pg975440xnvu14sdmx31toyty76fxy.png)